(untitled) (Research, Society and Development, 2021)
Introduction: The cerebrovascular accident (CVA) is a very prevalent event in the world population, and among its sequelae, muscle spasticity and paralysis stand out. Botulinum toxin is a pharmacological technique that brings beneficial effects to patients with spasticity, such as gain in range of motion and improvement in the function of affected limbs. Objective: to identify the evidence regarding the use of this toxin in these patients, especially in the face of muscle spasticity, an event strongly related to a stroke. Methodology: This is a descriptive research of the integrative literature review type, which seeks evidence on the use of botulinum toxin for the treatment of stroke sequelae. The search was conducted using PubMed, MEDLINE, Scielo, CDSR, Google Scholar, BVS and EBSCO databases, from 2003 to 2021. Thus, 26 scientific productions were totaled for the integrative literature review. Results: the treatment of spasticity with botulinum toxin is more successful when the administration follows some criteria such as: dose adjustment according to age, weight, degree of spasticity and musculature administered. Conclusion: the application of this toxin, combined with continued physical therapy, is the treatment of first choice for muscle spasticity, particularly in patients with sequelae after stroke, in order to increase mobility, range of motion, facilitate the performance of hygiene and other functional activities, improve immobilization wear and pain, and, thus, improve the quality of life of these patients.